Selective recovery of native copper from basalt tailings using alkaline glycinate solution - Wei Xiong; Jonathan Yang; Sophia Bauer (Applied Geochemistry, 2025)

Regional Processes Mediate Ecological Selection and the Distribution of Plant Diversity Across Scales - Christopher P. Catano; Jonathan Bauer; Tyler Bassett; Eric Behrens; Lars A. Brudvig (Ecology Letters, 2025)
Community ecology remains focused on interactions at small scales, which limits causal understanding of how regional and local processes interact to mediate biodiversity changes. We hypothesise that species pool size and immigration are two regional processes altering the balance between local niche selection and drift that cause variation in plant diversity. We manipulated the richness and number of seeds sown (species pool size and immigration respectively) into 12 grasslands across a landscape soil moisture gradient. Greater immigration and smaller species pools increased the variation in plant composition explained by soil moisture gradients but resulted in greater erosion of plant α ‐diversity and spatial β ‐diversity over time. Our results suggest that regional constraints on colonisation make community assembly more variable but help maintain species diversity by limiting biotic homogenisation. This study provides large‐scale experimental evidence on how regional contexts can alter the relative importance of fundamental processes shaping biodiversity change across scales.

A model for community-driven development of best practices: the Ocean Observatories Initiative Biogeochemical Sensor Data Best Practices and User Guide - Hilary I. Palevsky; Sophie Clayton; Heather Benway; Mairead Maheigan; Dariia Atamanchuk; Roman Battisti; Jennifer Batryn; Annie Bourbonnais; Ellen M. Briggs; Filipa Carvalho; Alison P. Chase; Rachel Eveleth; et al. (Frontiers in Marine Science, 2024)
The field of oceanography is transitioning from data-poor to data-rich, thanks in part to increased deployment of in-situ platforms and sensors, such as those that instrument the US-funded Ocean Observatories Initiative (OOI). However, generating science-ready data products from these sensors, particularly those making biogeochemical measurements, often requires extensive end-user calibration and validation procedures, which can present a significant barrier. Openly available community-developed and -vetted Best Practices contribute to overcoming such barriers, but collaboratively developing user-friendly Best Practices can be challenging. Here we describe the process undertaken by the NSF-funded OOI Biogeochemical Sensor Data Working Group to develop Best Practices for creating science-ready biogeochemical data products from OOI data, culminating in the publication of the GOOS-endorsed OOI Biogeochemical Sensor Data Best Practices and User Guide. For Best Practices related to ocean observatories, engaging observatory staff is crucial, but having a “user-defined” process ensures the final product addresses user needs. Our process prioritized bringing together a diverse team and creating an inclusive environment where all participants could effectively contribute. Incorporating the perspectives of a wide range of experts and prospective end users through an iterative review process that included “Beta Testers’’ enabled us to produce a final product that combines technical information with a user-friendly structure that illustrates data analysis pipelines via flowcharts and worked examples accompanied by pseudo-code. Our process and its impact on improving the accessibility and utility of the end product provides a roadmap for other groups undertaking similar community-driven activities to develop and disseminate new Ocean Best Practices.

Mechanisms for generating elevated zircon δ18O in Archean crust: Insights from the Saglek-Hebron Complex, Canada - Emily E. Mixon; Ann M. Bauer; Jonathan O'Neil; Hanika Rizo; Tyler B. Blum; John W. Valley; Chloë E. Bonamici (Earth and Planetary Science Letters, 2023)

Higher body weight-dependent neural activation during reward processing - Maike Richter; Sophia Widera; Franziska Malz; Janik Goltermann; Lavinia Steinmann; Anna Kraus; Verena Enneking; Susanne Meinert; Jonathan Repple; Ronny Redlich; Elisabeth J. Leehr; Dominik Grotegerd; et al. (Brain Imaging and Behavior, 2023)
Obesity is associated with alterations in brain structure and function, particularly in areas related to reward processing. Although brain structural investigations have demonstrated a continuous association between higher body weight and reduced gray matter in well-powered samples, functional neuroimaging studies have typically only contrasted individuals from the normal weight and obese body mass index (BMI) ranges with modest sample sizes. It remains unclear, whether the commonly found hyperresponsiveness of the reward circuit can (a) be replicated in well-powered studies and (b) be found as a function of higher body weight even below the threshold of clinical obesity. 383 adults across the weight spectrum underwent functional magnetic resonance imaging during a common card-guessing paradigm simulating monetary reward. Multiple regression was used to investigate the association of BMI and neural activation in the reward circuit. In addition, a one-way ANOVA model comparing three weight groups (normal weight, overweight, obese) was calculated. Higher BMI was associated with higher reward response in the bilateral insula. This association could no longer be found when participants with obesity were excluded from the analysis. The ANOVA revealed higher activation in obese vs. lean, but no difference between lean and overweight participants. The overactivation of reward-related brain areas in obesity is a consistent finding that can be replicated in large samples. In contrast to brain structural aberrations associated with higher body weight, the neurofunctional underpinnings of reward processing in the insula appear to be more pronounced in the higher body weight range.

Intraspecific variation in mycorrhizal response is much larger than ecological literature suggests - Katherine N. Stahlhut; Megan Conway; Chase M. Mason; Jonathan T. Bauer (Ecology, 2023)
Mycorrhizal response is the most common metric for characterizing how much benefit a plant derives from mycorrhizal symbiosis. Traditionally, ecologists have used these metrics to generalize benefit from mycorrhizal symbiosis in plant species, ignoring the potential for plant intraspecific trait variation to alter the outcome of the mutualism. In order for mean trait values to be useful as a functional trait to describe a species, as has been attempted for mycorrhizal response traits, interspecific variation must be much larger than intraspecific variation. While the variation among species has been extensively studied with respect to mycorrhizal response traits, variation within species has rarely been examined. We conducted a systematic review and analyzed how much variation for mycorrhizal growth and nutrient response typically exists within a plant species. We assessed 28 publications that included 60 individual studies testing mycorrhizal response in at least five genotypes of a plant species, and we found that intraspecific trait variation for mycorrhizal response was generally very large and highly variable depending on study design. The difference between the highest and lowest growth response in a study ranged from 10% to 350% across studies, and 36 of the studies included species for which both positive and negative growth responses to mycorrhizae were observed across different genotypes. The intraspecific variation for mycorrhizal growth response in some of these studies was larger than the variation documented among species across the plant kingdom. Phosphorus concentration and content was measured in 17 studies and variation in phosphorus response was similar to variation in growth responses. We also found that plant genotype was just as important for predicting mycorrhizal response as the effects of fungal inoculant identity. Our analysis highlights not only the potential importance of intraspecific trait variation for mycorrhizal response, but also the lack of research that has been done on the scale of this variation in plant species. Including intraspecific variation into research on the interactions between plants and their symbionts can increase our understanding of plant coexistence and ecological stability.

Ultraconserved elements-based phylogenomic systematics of the snake superfamily Elapoidea, with the description of a new Afro-Asian family - Sunandan Das; Eli Greenbaum; Shai Meiri; Aaron M. Bauer; Frank T. Burbrink; Christopher J. Raxworthy; Jeffrey L. Weinell; Rafe M. Brown; Jonathan Brecko; Olivier S.G. Pauwels; Nirhy Rabibisoa; Achille P. Raselimanana; et al. (Molecular Phylogenetics and Evolution, 2023)

The diverse role of heparan sulfate and other GAGs in SARS-CoV-2 infections and therapeutics - Friederike Eilts; Sarah Bauer; Keith Fraser; Jonathan S. Dordick; Michael W. Wolff; Robert J. Linhardt; Fuming Zhang (Carbohydrate Polymers, 2023)

Conspecific leaf litter induces negative feedbacks in Asteraceae seedlings - Max M. Zaret; Jonathan T. Bauer; Keith Clay; Briana K. Whitaker (Ecology, 2021)
The plant soil feedback (PSF) framework has been instrumental in understanding the impacts of soil microbes on plant fitness and species coexistence. PSFs develop when soil microbial communities are altered due to the identity and density of a particular plant species, which can then enhance or inhibit the local survival and growth of that plant species as well as different plant species. The recent extension of the PSF framework to aboveground microbiota, termed here as plant phyllosphere feedbacks (PPFs), can also help to determine the impact of aboveground microbes on plant fitness and species interactions. However, experimental tests of PPFs during early plant growth are nascent and the prevalence of PPFs across diverse plant species remains unknown. Additionally, it is unclear whether plant host characteristics, such as functional traits or phylogenetic distance, may help to predict the strength and direction of PPFs. To test for the prevalence of litter‐mediated PPFs, recently senesced plant litter from 10 native Asteraceae species spanning a range of life history strategies was used to inoculate seedlings of both conspecific and heterospecific species. We found that exposure to conspecific litter significantly reduced the growth of four species relative to exposure to heterospecific litter (i.e., significant negative PPFs), three species experienced marginally significant negative PPFs, and the PPF estimates for all 10 species were negative. However, neither plant functional traits, nor phylogenetic distance were predictive of litter feedbacks across plant species pairs, suggesting that other mechanisms or traits not measured may be driving conspecific negative PPFs. Our results indicate that negative, litter‐mediated PPFs are common among native Asteraceae species and that they may have substantial impacts on plant growth and plant species interactions, particularly during early plant growth.

Intra‐species genetic variability drives carbon metabolism and symbiotic host interactions in the ectomycorrhizal fungus Pisolithus microcarpus - Krista L. Plett; Annegret Kohler; Teresa Lebel; Vasanth R. Singan; Diane Bauer; Guifen He; Vivian Ng; Igor V. Grigoriev; Francis Martin; Jonathan M. Plett; Ian C. Anderson (Environmental Microbiology, 2021)
Summary Ectomycorrhizal (ECM) fungi are integral to boreal and temperate forest ecosystem functioning and nutrient cycling. ECM fungi, however, originate from diverse saprotrophic lineages and the impacts of genetic variation across species, and especially within a given ECM species, on function and interactions with the environment is not well understood. Here, we explore the extent of intra‐species variation between four isolates of the ECM fungus Pisolithus microcarpus , in terms of gene regulation, carbon metabolism and growth, and interactions with a host, Eucalyptus grandis . We demonstrate that, while a core response to the host is maintained by all of the isolates tested, they have distinct patterns of gene expression and carbon metabolism, resulting in the differential expression of isolate‐specific response pathways in the host plant. Together, these results highlight the importance of using a wider range of individuals within a species to understand the broader ecological roles of ECM fungi and their host interactions.

A Continuum of Evolving De Novo Genes Drives Protein-Coding Novelty in Drosophila - Brennen Heames; Jonathan Schmitz; Erich Bornberg-Bauer (Journal of Molecular Evolution, 2020)
Orphan genes, lacking detectable homologs in outgroup species, typically represent 10–30% of eukaryotic genomes. Efforts to find the source of these young genes indicate that de novo emergence from non-coding DNA may in part explain their prevalence. Here, we investigate the roots of orphan gene emergence in the Drosophila genus. Across the annotated proteomes of twelve species, we find 6297 orphan genes within 4953 taxon-specific clusters of orthologs. By inferring the ancestral DNA as non-coding for between 550 and 2467 (8.7–39.2%) of these genes, we describe for the first time how de novo emergence contributes to the abundance of clade-specific Drosophila genes. In support of them having functional roles, we show that de novo genes have robust expression and translational support. However, the distinct nucleotide sequences of de novo genes, which have characteristics intermediate between intergenic regions and conserved genes, reflect their recent birth from non-coding DNA. We find that de novo genes encode more disordered proteins than both older genes and intergenic regions. Together, our results suggest that gene emergence from non-coding DNA provides an abundant source of material for the evolution of new proteins. Following gene birth, gradual evolution over large evolutionary timescales moulds sequence properties towards those of conserved genes, resulting in a continuum of properties whose starting points depend on the nucleotide sequences of an initial pool of novel genes.

Concurrent improvement and deterioration of epilimnetic water quality in an oligotrophic lake over 37 years - William D. Hintz; Matthew S. Schuler; Jonathan J. Borrelli; Lawrence W. Eichler; Aaron B. Stoler; Vincent W. Moriarty; Laurie E. Ahrens; Charles W. Boylen; Sandra A. Nierzwicki‐Bauer; Rick A. Relyea (Limnology and Oceanography, 2020)
Single‐lake studies offer an opportunity for understanding, predicting, and mitigating local or regional threats to lake ecosystems. Our goal was to understand how concurrent environmental stressors such as climate change, eutrophication, and salinization affect long‐term lake water quality. We report epilimnetic changes in 18 water‐quality parameters collected at seven sites from 1980 to 2016 in Lake George, a large oligotrophic lake in the Adirondack Park, New York, USA. Improvements and deteriorations in water quality occurred over 37 years. We observed a 32% increase in chlorophyll a associated with an increase in orthophosphate, but not total phosphorus or a warming epilimnion (0.05°C/year). Salinization from road deicing salts contributed to the largest deterioration in water quality. However, chloride concentrations and the current rate of increase are low enough that few ecological impacts are likely to occur over the next few decades. Increasing calcium concentrations were not high enough to facilitate the persistence of invasive species in the lake such as zebra mussels ( Dreissena polymorpha ) but are sufficient for Asian clams ( Corbicula fluminea ) and the spiny water flea ( Bythotrephes longimanus ). Similar to other lakes, environmental legislation has supported recovery from acidification, indicated by reduced sulfate and nitrate, and increased alkalinity and pH. Declines in water quality were minor relative to other lakes, suggesting that decades of tourism and development occurred without major deterioration in water quality, but management efforts are needed to curb salinization in the Lake George watershed, particularly as it relates to sodium concentrations to prevent a loss of drinking water quality.

Local adaptation of mycorrhizae communities changes plant community composition and increases aboveground productivity - Jonathan T. Bauer; Liz Koziol; James D. Bever (Oecologia, 2020)

The global biogeography of lizard functional groups - Enav Vidan; Maria Novosolov; Aaron M. Bauer; Fernando Castro Herrera; Laurent Chirio; Cristiano de Campos Nogueira; Tiffany M. Doan; Amir Lewin; Danny Meirte; Zoltan T. Nagy; Daniel Pincheira‐Donoso; Oliver J.S. Tallowin; et al. (Journal of Biogeography, 2019)
Aim Understanding the mechanisms determining species richness is a primary goal of biogeography. Richness patterns of sub‐groups within a taxon are usually assumed to be driven by similar processes. However, if richness of distinct ecological strategies respond differently to the same processes, inferences made for an entire taxon may be misleading. We deconstruct the global lizard assemblage into functional groups and examine the congruence among richness patterns between them. We further examine the species richness – functional richness relationship to elucidate the way functional diversity contributes to the overall species richness patterns. Location Global. Methods Using comprehensive biological trait databases we classified the global lizard assemblage into ecological strategies based on body size, diet, activity times and microhabitat preferences, using Archetypal Analysis. We then examined spatial gradients in the richness of each strategy at the one‐degree grid cell, biome, and realm scales. Results We found that lizards can best be characterized by seven “ecological strategies”: scansorial , terrestrial , nocturnal , herbivorous , fossorial , large, and semi‐aquatic . There are large differences among the global richness patterns of these strategies. While the major richness hotspot for lizards in general is in Australia, several strategies exhibit highest richness in the Amazon Basin. Importantly, the global maximum in lizard species richness is achieved at intermediate values of functional diversity and increasing functional diversity further result in a slow decline of species richness. Main conclusions The deconstruction of the global lizard assemblage along multiple ecological axes offers a new way to conceive lizard diversity patterns. It suggests that local lizard richness mostly increases when species belonging to particular ecological strategies become hyper‐diverse there, and not because more ecological types are present in the most species rich localities. Thus maximum richness and maximum ecological diversity do not overlap. These results shed light on the global richness pattern of lizards, and highlight previously unidentified spatial patterns in understudied functional groups.

When and where plant‐soil feedback may promote plant coexistence: a meta‐analysis - Kerri M. Crawford; Jonathan T. Bauer; Liza S. Comita; Maarten B. Eppinga; Daniel J. Johnson; Scott A. Mangan; Simon A. Queenborough; Allan E. Strand; Katharine N. Suding; James Umbanhowar; James D. Bever (Ecology Letters, 2019)
Plant‐soil feedback (PSF) theory provides a powerful framework for understanding plant dynamics by integrating growth assays into predictions of whether soil communities stabilise plant–plant interactions. However, we lack a comprehensive view of the likelihood of feedback‐driven coexistence, partly because of a failure to analyse pairwise PSF, the metric directly linked to plant species coexistence. Here, we determine the relative importance of plant evolutionary history, traits, and environmental factors for coexistence through PSF using a meta‐analysis of 1038 pairwise PSF measures. Consistent with eco‐evolutionary predictions, feedback is more likely to mediate coexistence for pairs of plant species (1) associating with similar guilds of mycorrhizal fungi, (2) of increasing phylogenetic distance, and (3) interacting with native microbes. We also found evidence for a primary role of pathogens in feedback‐mediated coexistence. By combining results over several independent studies, our results confirm that PSF may play a key role in plant species coexistence, species invasion, and the phylogenetic diversification of plant communities.

Simulation of the 2003 Foss Barge - Point Wells Oil Spill: A Comparison between BLOSOM and GNOME Oil Spill Models - Rodrigo Duran; Lucy Romeo; Jonathan Whiting; Jason Vielma; Kelly Rose; Amoret Bunn; Jennifer Bauer (Journal of Marine Science and Engineering, 2018)
The Department of Energy’s (DOE’s) National Energy Technology Laboratory’s (NETL’s) Blowout and Spill Occurrence Model (BLOSOM), and the National Oceanic and Atmospheric Administration’s (NOAA’s) General NOAA Operational Modeling Environment (GNOME) are compared. Increasingly complex simulations are used to assess similarities and differences between the two models’ components. The simulations presented here are forced by ocean currents from a Finite Volume Community Ocean Model (FVCOM) implementation that has excellent skill in representing tidal motion, and with observed wind data that compensates for a coarse vertical ocean model resolution. The comprehensive comparison between GNOME and BLOSOM presented here, should aid modelers in interpreting their results. Beyond many similarities, aspects where both models are distinct are highlighted. Some suggestions for improvement are included, e.g., the inclusion of temporal interpolation of the forcing fields (BLOSOM) or the inclusion of a deflection angle option when parameterizing wind-driven processes (GNOME). Overall, GNOME and BLOSOM perform similarly, and are found to be complementary oil spill models. This paper also sheds light on what drove the historical Point Wells spill, and serves the additional purpose of being a learning resource for those interested in oil spill modeling. The increasingly complex approach used for the comparison is also used, in parallel, to illustrate the approach an oil spill modeler would typically follow when trying to hindcast or forecast an oil spill, including detailed technical information on basic aspects, like choosing a computational time step. We discuss our successful hindcast of the 2003 Point Wells oil spill that, to our knowledge, had remained unexplained. The oil spill models’ solutions are compared to the historical Point Wells’ oil trajectory, in time and space, as determined from overflight information. Our hindcast broadly replicates the correct locations at the correct times, using accurate tide and wind forcing. While the choice of wind coefficient we use is unconventional, a simplified analytic model supported by observations, suggests that it is justified under this study’s circumstances. We highlight some of the key oceanographic findings as they may relate to other oil spills, and to the regional oceanography of the Salish Sea, including recommendations for future studies.

The Influence of Oyster Farming on Sediment Bacterial Communities - Sarah G. Feinman; Yuna R. Farah; Jonathan M. Bauer; Jennifer L. Bowen (Estuaries and Coasts, 2018)

The dynamic life of arbuscular mycorrhizal fungal symbionts - Elizabeth M. Bach; Giselle Narvaez‐Rivera; Kira Murray; Jonathan T. Bauer; Kirsten S. Hofmockel (Ecology, 2018)

TGFβ counteracts LYVE-1-mediated induction of lymphangiogenesis by small hyaluronan oligosaccharides - Jochen Bauer; Melanie Rothley; Anja Schmaus; Luca Quagliata; Markus Ehret; Moritz Biskup; Véronique Orian-Rousseau; David G. Jackson; Ronald J. Pettis; Alfred Harvey; Stefan Bräse; Wilko Thiele; et al. (Journal of Molecular Medicine, 2018)

The Eurasian hot nightlife: Environmental forces associated with nocturnality in lizards - Enav Vidan; Uri Roll; Aaron Bauer; Lee Grismer; Peng Guo; Erez Maza; Maria Novosolov; Roberto Sindaco; Philipp Wagner; Jonathan Belmaker; Shai Meiri (Global Ecology and Biogeography, 2017)
Aim Lizards are ancestrally diurnal, and most of them remain so. Nocturnality is common among lizards, but the environmental factors associated with lizard nocturnal activity are still unknown. Here, we contrasted the ambient temperature and productivity hypotheses, where we predicted that cold temperatures will pose a stonger limit to nocturnal species richness than diurnal lizards. Moreover, we contrasted the relative importance of annual, day and night mean temperatures to pinpoint the drivers of nocturnal lizard richness. Location Mainland Eurasia. Methods We collected distribution range and activity time data for all 1,113 lizard species found throughout mainland Eurasia. This represents the largest geographical scope to date, for studies of lizard species richness. We examined the spatial patterns of nocturnal species richness in relationship to diurnal species richness across environmental gradients of ambient temperature and productivity. Results Nocturnal lizards are richest in the tropics and in deserts, and their richness decreases with latitude. However, nocturnal lizards are absent from the highest latitudes and coldest regions inhabited by lizards. Diurnal and nocturnal lizards respond in a similar manner to climatic factors. Ambient temperature has a strong influence on both, whereas productivity is more tightly related to the proportion of nocturnal species. Main conclusions Nocturnality is widespread among Eurasian lizards. However, nocturnal lizards are absent from invariably cold regions, and low temperatures seem to be a limiting factor for lizard activity period. We suggest that the year‐round warm nights of the tropics reduce the cost of being active at night and open the nocturnal niche for many lizards. In hot deserts, the combination of hot days and aridity increases the cost of diurnal activity, whereas nocturnal activity provides a shelter from these extreme conditions.

Negative plant‐phyllosphere feedbacks in native Asteraceae hosts – a novel extension of the plant‐soil feedback framework - Briana K. Whitaker; Jonathan T. Bauer; James D. Bever; Keith Clay (Ecology Letters, 2017)
Over the past 25 years, the plant‐soil feedback (PSF) framework has catalyzed our understanding of how belowground microbiota impact plant fitness and species coexistence. Here, we apply a novel extension of this framework to microbiota associated with aboveground tissues, termed ‘plant‐phyllosphere feedback (PPFs)’. In parallel greenhouse experiments, rhizosphere and phyllosphere microbiota of con‐ and heterospecific hosts from four species were independently manipulated. In a third experiment, we tested the combined effects of soil and phyllosphere feedback under field conditions. We found that three of four species experienced weak negative PSF whereas, in contrast, all four species experienced strong negative PPFs. Field‐based feedback estimates were highly negative for all four species, though variable in magnitude. Our results suggest that phyllosphere microbiota, like rhizosphere microbiota, can potentially mediate plant species coexistence via negative feedbacks. Extension of the PSF framework to the phyllosphere is needed to more fully elucidate plant‐microbiota interactions.

Patterns of species richness, endemism and environmental gradients of African reptiles - Amir Lewin; Anat Feldman; Aaron M. Bauer; Jonathan Belmaker; Donald G. Broadley; Laurent Chirio; Yuval Itescu; Matthew LeBreton; Erez Maza; Danny Meirte; Zoltán T. Nagy; Maria Novosolov; et al. (Journal of Biogeography, 2016)
Aim To map and assess the richness patterns of reptiles (and included groups: amphisbaenians, crocodiles, lizards, snakes and turtles) in Africa, quantify the overlap in species richness of reptiles (and included groups) with the other terrestrial vertebrate classes, investigate the environmental correlates underlying these patterns, and evaluate the role of range size on richness patterns. Location Africa. Methods We assembled a data set of distributions of all African reptile species. We tested the spatial congruence of reptile richness with that of amphibians, birds and mammals. We further tested the relative importance of temperature, precipitation, elevation range and net primary productivity for species richness over two spatial scales (ecoregions and 1° grids). We arranged reptile and vertebrate groups into range‐size quartiles in order to evaluate the role of range size in producing richness patterns. Results Reptile, amphibian, bird and mammal richness are largely congruent ( r = 0.79–0.86) and respond similarly to environmental variables (mainly productivity and precipitation). Ecoregion size accounts for more variation in the richness of reptiles than in that of other groups. Lizard distributions are distinct with several areas of high species richness where other vertebrate groups (including snakes) are species‐poor, especially in arid ecoregions. Habitat heterogeneity is the best predictor of narrow‐ranging species, but remains relatively important in explaining lizard richness even for species with large range sizes. Main conclusions Reptile richness varies with similar environmental variables as the other vertebrates in Africa, reflecting the disproportionate influence of snakes on reptile richness, a result of their large ranges. Richness gradients of narrow‐ranged vertebrates differ from those of widespread taxa, which may demonstrate different centres of endemism for reptile subclades in Africa. Lizard richness varies mostly with habitat heterogeneity independent of range size, which suggests that the difference in response of lizards is due to their ecological characteristics. These results, over two spatial scales and multiple range‐size quartiles, allow us to reliably interpret the influence of environmental variables on patterns of reptile richness and congruency.

The Carbon Footprint of Games Distribution - Kieren Mayers; Jonathan Koomey; Rebecca Hall; Maria Bauer; Chris France; Amanda Webb (Journal of Industrial Ecology, 2015)
Summary This research investigates the carbon footprint of the lifecycle of console games, using the example of PlayStation®3 distribution in the UK. We estimate total carbon equivalent emissions for an average 8.8‐gigabyte (GB) game based on data for 2010. The bulk of emissions are accounted for by game play, followed by production and distribution. Two delivery scenarios are compared: The first examines Blu‐ray discs (BDs) delivered by retail stores, and the second, games files downloaded over broadband Internet. Contrary to findings in previous research on music distribution, distribution of games by physical BDs results in lower greenhouse gas emissions than by Internet download. The estimated carbon emissions from downloading only fall definitively below that of BDs for games smaller than 1.3 GB. Sensitivity analysis indicates that as average game file sizes increase, and the energy intensity of the Internet falls, the file size at which BDs would result in lower emissions than downloads could shift either up‐ or downward over the next few years. Overall, the results appear to be broadly applicable to title games within the European Union (EU), and for larger‐than‐average sized games in the United States. Further research would be needed to confirm whether similar findings would apply in future years with changes in game size and Internet efficiency. The study findings serve to illustrate why it is not always true that digital distribution of media will have lower carbon emissions than distribution by physical means when file sizes are large.

Sugars in the microenvironment: the sticky problem of HA turnover in tumors - Anja Schmaus; Jochen Bauer; Jonathan P. Sleeman (Cancer and Metastasis Reviews, 2014)

Plant-soil feedbacks between invasive shrubs and native forest understory species lead to shifts in the abundance of mycorrhizal fungi - Sarah M. Shannon; Jonathan T. Bauer; Wendy E. Anderson; Heather L. Reynolds (Plant and Soil, 2014)

Long-term legacies and partial recovery of mycorrhizal communities after invasive plant removal - Richard A. Lankau; Jonathan T. Bauer; M. Rebecca Anderson; Roger C. Anderson (Biological Invasions, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Context dependency of the allelopathic effects of Lonicera maackii on seed germination - Jonathan T. Bauer; Sarah M. Shannon; Rebecca E. Stoops; Heather L. Reynolds (Plant Ecology, 2012)

Nitrogen-fixing bacteria, arbuscular mycorrhizal fungi, and the productivity and structure of prairie grassland communities - Jonathan T. Bauer; Nathan M. Kleczewski; James D. Bever; Keith Clay; Heather L. Reynolds (Oecologia, 2012)

Invasive species: “back-seat drivers” of ecosystem change? - Jonathan T. Bauer (Biological Invasions, 2012)

Millennial‐aged organic carbon subsidies to a modern river food web - Nina Caraco; James E. Bauer; Jonathan J. Cole; Steven Petsch; Peter Raymond (Ecology, 2010)
Recent studies indicate that highly aged material is a major component of organic matter transported by most rivers. However, few studies have used natural 14 C to trace the potential entry of this aged material into modern river food webs. Here we use natural abundance 14 C, 13 C, and deuterium ( 2 H) to trace the contribution of aged and contemporary organic matter to an important group of consumers, crustacean zooplankton, in a large temperate river (the Hudson River, New York, USA). Zooplankton were highly 14 C depleted (mean Δ 14 C = −240‰) compared to modern primary production in the river or its watershed (Δ 14 C = −60‰ to +50‰). In order to account for the observed 14 C depletion, zooplankton must be subsidized by highly aged particulate organic carbon. IsoSource modeling suggests that the range of the aged dietary subsidy is between ~57%, if the aged organic matter source was produced 3400 years ago, and ~21%, if the organic carbon used is ≥50 000 years in age, including fossil material that is millions of years in age. The magnitude of this aged carbon subsidy to river zooplankton suggests that modern river food webs may in some cases be buffered from the limitations set by present‐day primary production.

A test for ectopic exchange catalyzed by Cre recombinase in maize - Thomas S. Ream; Jonathan Strobel; Brandon Roller; Donald L. Auger; Akio Kato; Cynthia Halbrook; Eric M. Peters; James Theuri; Matthew J. Bauer; Prince Addae; Waly Dioh; Jeffrey M. Staub; et al. (Theoretical and Applied Genetics, 2005)

Atmospheric CO 2 evasion, dissolved inorganic carbon production, and net heterotrophy in the York River estuary - Peter A. Raymond; James E. Bauer; Jonathan J. Cole (Limnology and Oceanography, 2000)
Direct measurements of the partial pressure of CO 2 (pCO 2 ) and dissolved inorganic carbon (DIC) were made over a 2‐yr period in surface waters of the York River estuary in Virginia. The pCO 2 in surface waters exceeded that in the overlying atmosphere, indicating that the estuary was a net source of CO 2 to the atmosphere at most times and locations. Salinity‐based DIC mixing curves indicate there was also an internal source of both DIC and alkalinity, implying net alkalinity generation within the estuary. The DIC and alkalinity source displayed seasonal patterns similar to that of pCO 2 and were reproducible over a 2‐yr study period. We propose that the source of inorganic carbon necessary for both the sustained CO 2 evasion to the atmosphere and the advective export of DIC is respiration in excess of primary production (e.g., net heterotrophy). The rates of CO 2 evasion and DIC export were estimated to provide an annual rate of net heterotrophy of ~100 g C m −2 yr −1 . Approximately 40% of this excess inorganic carbon production was exported as DIC to the coastal ocean, whereas 60% was lost as CO 2 evasion to the atmosphere. The alkalinity generation needed to sustain the export of inorganic carbon, as HCO 3 − , is most likely provided by net sulfate reduction in sediments. Accumulation of sulfide in the sediments of a representative site directly adjacent to the York River estuary is sufficient to account for the net export of alkalinity. The seasonality of net heterotrophy causes large variations in annual CO 2 and DIC concentrations, and it stresses the need for comprehensive temporal data sets when reporting annual rates of CO 2 evasion, DIC advection, and net heterotrophy.